On Whether Euthanasia in China Should Be Legalized - Liu, Si (International Journal of Social Sciences and Public Administration, 2024)
The term euthanasia originated in Greece and originally meant "to die happily.". With the progress of social technology and the development of ethics and morality, more and more people are beginning to support euthanasia, which means a "happy" and "painless" death, thereby reducing the pain of patients and reflecting end-of-life care for them. At present, countries such as the Netherlands, Belgium, Japan, Switzerland, Canada, etc. have enacted laws on euthanasia, while China currently does not have relevant regulations. This article will discuss whether euthanasia in China should be legalized.